Using non-lexicalised pauses as self-assessment metacognitive strategies to enhance speech production - Komalah Tharmalingam,; Adelina Asmawi,; Lim, Jia Wei (Penerbit Universiti Kebangsaan Malaysia, 2024)
Speech experts consider non-lexicalised pauses as speakers’ cognitive actions to monitor, evaluate and enhance their speech outputs. Although these actions are linked to self-assessment, speakers’ self-assessment skills in English as a Second Language-speaking contexts are often confined to how they utilise assessment rubrics, checklists and teacher commentaries. Since, in reality, speaking is impromptu and individuals have limited access to these assessment standards and commentaries, this exploratory case study aims to unpack the self-assessment metacognitive strategies that intermediate and low proficiency level students use while employing their non-lexicalised pauses in impromptu speech. Through purposive sampling, three participants from each proficiency level were selected, and they partook in two ten-minute video-recorded group discussions. The non-lexicalised pauses in their discussions were the reference points for the stimulated-recall interviews; meanwhile, video recordings supplemented their interview responses. A conceptual framework based on O'Malley and Chamot’s (1990) metacognitive strategies and Kormos's (2006) speech production model was adopted from past studies to thematically analyse the research data. The analysis found Case I (intermediate proficiency) participants utilised two self-assessment metacognitive strategies— organisational planning and self-monitoring—whereas Case L (low proficiency) participants used one strategy—self-monitoring—while employing the non-lexicalised pauses. Participants' L2 mastery and contextual factors significantly influenced their choice of strategies. Despite some limitations, the findings indicated that participants in Cases I and L applied their readily accessible resources to self-assess impromptu speech metacognitively. Additionally, the analysis suggests that speech dysfluency should not be deemed speakers' speaking incompetence but rather self-assessment strategies to improve their speech quality